2021
DOI: 10.3390/brainsci11091236
|View full text |Cite
|
Sign up to set email alerts
|

Processing Aspectual Agreement in an Inflexionless Language: An ERP Study of Mandarin Chinese

Abstract: This is a study of the collocation of Chinese verbs with different lexical aspects and aspect markers. Using event-related potentials (ERPs), we explored the processing of aspect violation sentences. In the experiment, we combined verbs of various lexical aspect types with the progressive aspect marker zhe, and the combination of the achievement verbs and the progressive aspect marker zhe constituted the sentence’s aspect violation. The participants needed to judge whether a sentence was correct after it was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Even though there is an important methodological difference between our study and two studies that focused on Mandarin Chinese, our results are in line with the findings of Zhang and Zhang (2008) and Hao, Xun and Lu (2021), which found the P600 for aspectual violations. BCS aspect violations, however, did not result in the N400-like component as in Hao, Xun and Lu (2021). Hao, Xun and Lu suggest that in sentences with aspectual violations the punctual lexical aspect of the verb creates expectations for non-progressive morphology.…”
Section: Processing Grammatical Aspect In Bcsmentioning
confidence: 91%
See 2 more Smart Citations
“…Even though there is an important methodological difference between our study and two studies that focused on Mandarin Chinese, our results are in line with the findings of Zhang and Zhang (2008) and Hao, Xun and Lu (2021), which found the P600 for aspectual violations. BCS aspect violations, however, did not result in the N400-like component as in Hao, Xun and Lu (2021). Hao, Xun and Lu suggest that in sentences with aspectual violations the punctual lexical aspect of the verb creates expectations for non-progressive morphology.…”
Section: Processing Grammatical Aspect In Bcsmentioning
confidence: 91%
“…That effect was followed by the P600 component as well as a late anterior negativity on the word immediately adjacent to the aspectual marker. Hao, Xun and Lu (2021) suggest that the mismatch between lexical aspect of the verb and grammatical aspect expressed by aspectual markers involved both semantic and syntactic processing, as reflected in the N400-like and the P600 components. The authors interpreted the late anterior negativity on the post-critical word as a secondary repair process that followed the repair process on the critical word indicated by the P600.…”
Section: Previous Studies On Aspect Processingmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, several studies revealed linguistic distance's effect on advanced CSL learners' implicit grammatical processing from an electrophysiological perspective. Hao et al (2022) used eventrelated potentials to investigate how linguistic distance affected advanced CSL learners from Indonesia and Thailand acquire Chinese "aspect" and discovered similar EEG patterns evoked by the two learner types for processing aspect violation sentences, but noted that even advanced CSL learners did not reach native speakers' automatic processing level. These studies hold that psychological typology, learning strategies, and other factors weaken the impact of L1 negative transfer, and they do not entirely deny the role of cross-language transfer.…”
Section: Linguistic Distance and Csl Acquisition 231 Qualitative Ling...mentioning
confidence: 99%
“…Linguistic distance is an important indicator of L1 and second language similarity, and thus an important independent variable in cross-language transfer studies. Many previous studies on acquiring Chinese as a second language (CSL) examined linguistic distance effects on Chinese character (Jiang, 2003;Zhang, 2017;Deng and Hu, 2022), vocabulary (Hong, 2013;Xu, 2014;Hsieh and Wang, 2020;Chai and Ma, 2022;Tang and Chan, 2022), and grammar (Yuan, 1998(Yuan, , 2004Wu and Zhao, 2018;Hao et al, 2022) acquisition. Chinese comprises several subsystems, such as Chinese character, vocabulary, and grammar, that interact across levels (De Saussure, 1959).…”
Section: Introductionmentioning
confidence: 99%